Penerapan Kebijakan Rekrutmen Peserta Didik dalam Meningkatkan Kualitas Pendidikan di Pondok Pesantren Musthafawiyah Purba Baru - Ummu Salamah; Novebri Novebri (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research examines the implementation of student recruitment policies at the Musthafawiyah Purba Baru Islamic Boarding School, North Sumatra, in order to improve the quality of education. As one of the largest Islamic boarding schools in Indonesia, Musthafawiyah faces the challenge of competition with other educational institutions in recruiting quality prospective students. This research uses a qualitative descriptive method with data collected through interviews, observation and documentation studies. The research results show that Musthafawiyah implemented a strict selection which included academic tests, Al-Quran reading and writing tests, and motivational interviews, to attract potential students. However, this policy faces obstacles in the form of negative public perceptions and limited resources. This research recommendation includes strategies to improve the promotion process and improve facilities to strengthen the attractiveness of Islamic boarding schools. By implementing strategic recruitment policies, it is hoped that Musthafawiyah will be able to maintain the quality of education and continue to attract the interest of prospective students from various regions.